Alfabetizar letrando: uma revisão de literatura sobre as possibilidades de êxito e desafios nos primeiros anos do Ensino Fundamental - Teles, Damares Araújo (2023)
The research addresses a study on literacy and literacy with the objective of analyzing, from the literature review, the literacy strategies proposed in research of Theses and Dissertations published in BDTD, between the years 2015 and 2023, and that address the literacy in the early years of elementary school. The course of the research was also guided by the specific objectives, namely: to identify the characteristics of each literacy strategy, highlighting the positive points for literacy; present a compilation of literacy strategies, and how they can be articulated to work on the concept of literacy through literacy and describe the possibilities for success and challenges in the first years of elementary school. The research is based on the following problem: Do the literacy strategies proposed in research of Theses and Dissertations published in BDTD, between the years 2015 and 2023, make it possible to teach literacy in the early years of elementary school? The theoretical basis of the research is composed of the contributions of Ferreiro and Teberosky (1999), Ferreiro (2005), Soares (2017), among others, who bring important studies on literacy and literacy. The methodological approach is qualitative, carried out by literature review and bibliographical research using the following techniques: document analysis and content analysis. The revealed data show that, on the one hand, there are significant teaching practices, with the use of strategies that were intended to develop a work from the perspective of teaching literacy and overcoming challenges so that the practices were effective. But on the other hand, there are teachers who did not plan differently, developing a homogeneous practice, without establishing diversified strategies. They did not seek alternatives to overcome the challenges encountered. They had many difficulties in carrying out the literacy work. Another important point was the emphasis on initial and continuing training of literacy teachers, which showed many weaknesses. These points show that teachers need to appropriate specific knowledge for the practice of literacy and need to be grounded in theories that help them to understand the processes that children go through in the construction of knowledge about written language. It is hoped that this work will contribute to the practice of teachers who already work in literacy and for those who will enter this path